Deposit collectors - Nava Ashraf; Dean S. Karlan; Wesley Yin (Yale University, Economic Growth Center, 2005)
Informal lending and savings institutions exist around the world, and often include regular door-to-door deposit collection of cash. Some banks have adopted similar services in order to expand access to banking services in areas that lack physical branches. Using a randomized control trial, we investigate determinants of participation in a deposit collection service and evaluate the impact of offering the service for micro-savers of a rural bank in the Philippines. Of 137 individuals offered the service in the treatment group, 38 agreed to sign-up, and 20 regularly used the service. Take-up is predicted by distance to the bank (a measure of transaction costs of depositing without the service) as well as being married (a suggestion that household bargaining issues are important). Those offered the service saved 188 pesos more (which equates to about a 25% increase in savings stock) and were slightly less likely to borrow from the bank.
Keywords: D1; D9; G1; G2; O1; 330; Savings behavior; microfinance; field experiment; savings mobilization; deposit collector